Global trends of esophageal cancer among individuals over 60 years: an epidemiological analysis from 1990 to 2050 based on the global burden of disease study 1990-2021 - Lu, Simiao; Li, Kexun; Wang, Kangning; Liu, Guangyuan; Han, Yongtao; Peng, Lin; Chen, Lei; Leng, Xuefeng (Oncology Reviews, 2025)
ObjectiveEsophageal cancer (EC) ranks as the sixth leading cause of cancer-related deaths globally, with over 500,000 new cases annually. Understanding trends in individuals over 60 is critical for enhancing treatment and the success of early diagnosis and screening.Materials and methodsThis study analyzed global, regional, and national trends in EC management among individuals aged 60 years and older, spanning from 1990 to 2021, utilizing data from the Global Burden of Disease Study 2021. We employed the integrating differential equations to enhance the accuracy of incidence, prevalence, mortality, and Disability-Adjusted Life Years (DALYs). The Bayesian Age-Period-Cohort (BAPC) model was also used to forecast future trends up to 2050.ResultsOur findings indicate significant shifts in the EC burden among those over 60, with a notable increase in absolute numbers from 1990 to 2021, despite a decline in age-standardized rates. The incidence rose by 185%, while the age-standardized prevalence rate decreased by 17.02%. Socioeconomic factors, indicated by the Social Demographic Index, revealed varying trends across different regions and income levels, highlighting the influence of economic status on EC outcomes.ConclusionAnalysis indicates varying trends across different regions. Behavioral risk factors, particularly smoking and alcohol use, significantly contribute to the burden of EC, especially among males. Projections suggest that despite declining age-standardized rates, the absolute number of cases, deaths, and DALYs will continue to rise due to population growth and aging, highlighting the ongoing global challenge of EC.